KEMAMPUAN LITERASI DIGITAL GURU DALAM PEMBELAJARAN MATEMATIKA SEKOLAH DASAR - Galuh Ajeng Nurazizah; Yepi Sedya Purwananti (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to describe the literacy skills of teachers in mathematics learning at SD Negeri 2 Gondosuli. The research method used in this study is a qualitative method with a descriptive research type. The location of the study was at SD Negeri 2 Gondosuli, Gondang District, Tulungagung Regency. The subjects of this study were 12 teachers at SD Negeri 2 Gondosuli. The data collection techniques for this study were observation, interviews, questionnaires, and documentation. The results of the study indicate that teachers who have digital literacy skills can be identified through their ability to use digital devices, search for information and digital learning resources, knowledge and skills in applying digital products, and attitudes and perspectives in digital literacy. In general, teacher competence in mathematics learning is good, especially in understanding digital technology and its implementation in learning. Teachers also have a positive perception of the influence of digital literacy on student learning outcomes, are able to facilitate digital collaborative learning, and identify obstacles and solutions in the use of digital technology. This study provides an important contribution as a reference for elementary school teachers to develop their digital literacy skills in order to improve the quality of learning in the digital era.